EFEKTIVITAS REKRUTMEN DAN SELEKSI DALAM MEMENUHI KEBUTUHAN TENAGA PERAWAT DI RSIA MUSLIMAT JOMBA - Arishinta Kumaladewi (Ma Chung Press, 2018)
Mother And Child Hospital (RSIA) Muslimat Jombang is a private hospital giving prime services. One of the ways to improve the Hospital services is by prioritizing on patient interest as well as on the management of services. Therefore, it is necessary to recruit competent employees and employees with good performance. The effective recruitment and selection process is greatly required so that the Hospital recruits the expected employees. This research aims to evaluate the effectiveness of nurse personnel recruitment and selection implementation in RSIA Muslimat Jombang, to know on the process and obstacles to be considered in the recruitment and selection, as well as recommend on the alternative of nurse personnel recruitment and selection implementation in a more effective manner so that these can be applied in RSIA Muslimat Jombang. This research uses qualitative method with sources of data, the data collection technique uses in-depth interview and documentation. The research results show that the implementation of recruitment applied in the Hospital for nurse personnel uses social media namely Facebook and reference from people inside the Hospital and friends. The Hospital yet develops a broader social media because of limitation on human resources, so that there is only a few number of applicants; it also causes less qualified and competent applicants. Out of 144 applicants, there are only 35 applicants passing the administration requirements and 6 applicants passing writing and practice test selection. This shows the small number of nurse applicant meeting the qualifications and the test results also are not based on the expected values. From the research results, these show that the recruitment and selection process for nurse personnel in RSIA Muslimat Jombang is not effective